2014
DOI: 10.7717/peerj.384
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of theSLC26A4,FOXI1andKCNJ10genes in individuals with congenital hearing loss

Abstract: Pendred syndrome (PDS) and DFNB4 comprise a phenotypic spectrum of sensorineural hearing loss disorders that typically result from biallelic mutations of the SLC26A4 gene. Although PDS and DFNB4 are recessively inherited, sequencing of the coding regions and splice sites of SLC26A4 in individuals suspected to be affected with these conditions often fails to identify two mutations. We investigated the potential contribution of large SLC26A4 deletions and duplications to sensorineural hearing loss (SNHL) by scre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…FOXI1 (OMIM #601093) is a transcription factor for SLC26A4 [ 52 , 53 ], and KCNJ10 (OMIM #602208) is an inwardly rectifying K + channel essential for the maintenance of the endocochlear potential [ 54 ]. Although later studies showed that sequence alterations in FOXI1 or KCNJ10 are rare in the context of PS/non-syndromic EVA [ 55 , 56 , 57 , 58 ], analysis of these genes may be of value in individuals with monoallelic pathogenic SLC26A4 sequence alterations.…”
Section: Discussionmentioning
confidence: 99%
“…FOXI1 (OMIM #601093) is a transcription factor for SLC26A4 [ 52 , 53 ], and KCNJ10 (OMIM #602208) is an inwardly rectifying K + channel essential for the maintenance of the endocochlear potential [ 54 ]. Although later studies showed that sequence alterations in FOXI1 or KCNJ10 are rare in the context of PS/non-syndromic EVA [ 55 , 56 , 57 , 58 ], analysis of these genes may be of value in individuals with monoallelic pathogenic SLC26A4 sequence alterations.…”
Section: Discussionmentioning
confidence: 99%
“…PDS is a complex genetic disease which may be inherited monogenically or digenically [ 4 , 9 11 ]. It has been well documented that biallelic mutations in SLC26A4 (MIM #605646) is the hallmark of PDS, with a frequency of 25% [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDS is a complex genetic disease which may be inherited monogenically or digenically [ 4 , 9 11 ]. It has been well documented that biallelic mutations in SLC26A4 (MIM #605646) is the hallmark of PDS, with a frequency of 25% [ 4 , 9 ]. Clinically, SLC26A4 mutation has been used as genetic test to differentiate between PDS and non-syndromic familial EVA, which otherwise would not be possible to clinically distinguish, even with perchlorate discharge test [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical features observed in PS typically result from biallelic (homozygote/compound heterozygote) mutations in the SLC26A4 gene. According to the Human Gene Mutation Database more than 260 mutations in the SLC26A4 gene have been identified to date 5 , including splice site aberrations, frame shift and nonsense mutations, as well as large deletions (rare cases) and a relatively common mutation, c.-103 T > C, in a regulatory element of the promoter region of the SLC26A4 gene 6 7 . The mutation spectrum of SLC26A4 varies widely among ethnic groups, with certain mutations demonstrating a higher prevalence in specific populations 8-11 .…”
Section: Introductionmentioning
confidence: 99%